2000
DOI: 10.1177/019251300021005003
|View full text |Cite
|
Sign up to set email alerts
|

Health Consequences of Marriage for the Retirement Years

Abstract: Greater numbers of persons will enter retirement outside of marriage or with a checkered marital history. Given the traditional health benefits of marriage, these changes in the population's marital life course may foretell changing demands for eldercare in addition to adverse health consequences. Here, the authors provide new evidence on the specific aspects of health associated with marriage for a nationally representative survey of retirement age adults. An important aspect of the authors' analysis is the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 31 publications
7
98
1
4
Order By: Relevance
“…From a social causation perspective, divorce may increase health risks by severing resources of marriage (Hughes and Waite 2009) or raising stress (Amato 2000;Williams and Umberson 2004). Consistent with this view, studies have documented a positive association between divorce and functional limitations (Hughes and Waite 2009;Liu and Zhang 2013;Pienta et al 2000), chronic illnesses (Molloy et al 2009), self-assessed health (Williams and Umberson 2004), and mortality (Dupre et al 2009;Hu and Goldman 1990;Lillard and Waite 1995;Rendall et al 2011;Shor et al 2012).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…From a social causation perspective, divorce may increase health risks by severing resources of marriage (Hughes and Waite 2009) or raising stress (Amato 2000;Williams and Umberson 2004). Consistent with this view, studies have documented a positive association between divorce and functional limitations (Hughes and Waite 2009;Liu and Zhang 2013;Pienta et al 2000), chronic illnesses (Molloy et al 2009), self-assessed health (Williams and Umberson 2004), and mortality (Dupre et al 2009;Hu and Goldman 1990;Lillard and Waite 1995;Rendall et al 2011;Shor et al 2012).…”
Section: Introductionmentioning
confidence: 88%
“…2 In a study of the effects of marital biography on health using the Health and Retirement Study (HRS), Hughes and Waite (2009) reported a positive association between divorce and mobility limitations among persons ages 51-62. Using the National Health Interview Survey (NHIS), Liu and Zhang (2013) found a positive link between divorce and disability, as measured by activities of daily living (ADLs) or instrumental activities of daily living (IADLs), among men at advanced older ages (see also Grundy and Holt (2000) and Pienta et al (2000)). Albeit useful, the prior literature has not focused on work disability.…”
Section: A Life Course Perspective On Disabilitymentioning
confidence: 99%
“…Marriage itself is an integrating role, one with clear emotional benefits to health (Pienta, Hayward, & Jenkins, 2000;Waite & Gallagher, 2000). Married persons are, by definition, less socially isolated than are those who are widowed, divorced, or never married.…”
Section: Marital Statusmentioning
confidence: 99%
“…Additionally, remarrying may increase the chances of improved physical and mental health status. Married persons in later life have the lowest rates of fatal and nonfatal diseases, disability, and physical functioning problems when compared to their divorced counterparts (Pienta, Hayward, & Jenkins, 2000). Remarried individuals generally report less distress than divorced individuals (Shapiro, 1996).…”
Section: Interrupted Career Divorcementioning
confidence: 98%